1995
DOI: 10.1088/0957-0233/6/2/010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of acoustic emission and electrical resistance variation in stress-corrosion cracking

Abstract: A measurement system that simultaneously digitizes acoustic emission pulses in stress-corrosion cracking processes and gauges the electrical resistance variations caused by crack growth has been developed. This tool has allowed us to study the relation between the magnitudes measured by the two systems in stress-corrosion cracking processes in high-strength low-alloy steels. The information provided by acoustic energy, number of bursts and number of acoustic emission counts is analysed, as is the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Barnett and Troiano [60] first used this technique for laboratory research to measure crack growth kinetics in a study of hydrogen embrittlement in notched tensile specimens. Electrical PD methods, which were also named as electrical resistance methods, have been used with success of detection crack closure in fatigue crack studies [61][62][63][64][65][66][67][68][69][70], crack initiation in crackopening displacement and fatigue tests [23,45,46,[71][72][73][74][75][76][77], measurement of crack growth under various of loading conditions (including fatigue [9,21,55,[78][79][80][81], creep [19,21,37,42,[81][82][83][84][85], stress corrosion [21,[86][87][88], sustained loading [89][90][91], fretting fatigue [12], and hydrogen embrittlement [21,…”
Section: Potential Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Barnett and Troiano [60] first used this technique for laboratory research to measure crack growth kinetics in a study of hydrogen embrittlement in notched tensile specimens. Electrical PD methods, which were also named as electrical resistance methods, have been used with success of detection crack closure in fatigue crack studies [61][62][63][64][65][66][67][68][69][70], crack initiation in crackopening displacement and fatigue tests [23,45,46,[71][72][73][74][75][76][77], measurement of crack growth under various of loading conditions (including fatigue [9,21,55,[78][79][80][81], creep [19,21,37,42,[81][82][83][84][85], stress corrosion [21,[86][87][88], sustained loading [89][90][91], fretting fatigue [12], and hydrogen embrittlement [21,…”
Section: Potential Differencementioning
confidence: 99%
“…3b and a basic description is given here. A noticeable improvement offered by the ACPD method is the introduction of phase sensitive detection associated with lock-in amplifiers that offer excellent noise rejection and improved accuracy and sensitivity for ACPD measurements [22,34,76,88,124,137,140]. In the excitation circuits a reference signal provided by a voltage controlled oscillator is fed into a power amplifier for constant current output [34,45,48,133,134,140,150].…”
Section: Experimental System Designsmentioning
confidence: 99%
“…One of the main difficulties in using the AE technique for EAC research is interpretation of the results obtained. The relationship between the extent of cracking (on both micro- and macroscopic levels), elastic energy released and the various mechanisms that intervene in crack growth are not well defined or characterised 40. However, several studies have shown that a qualitative relationship exists between AE activity and severity of IG SCC (Fig.…”
Section: Acoustic Emissionmentioning
confidence: 99%
“…This method is sensitive and has continuous monitoring capabilities [12][13][14]. It has been utilized as a measurement tool to assess the health condition of materials [15][16][17][18]. Santos-Leal et al [15] developed a simultaneous measurement system to investigate the relation between the information measured by AE and electrical resistance variation during the stress corrosion crack propagation in high-strength low-alloy steels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been utilized as a measurement tool to assess the health condition of materials [15][16][17][18]. Santos-Leal et al [15] developed a simultaneous measurement system to investigate the relation between the information measured by AE and electrical resistance variation during the stress corrosion crack propagation in high-strength low-alloy steels. The results indicated the cumulative counts and cumulative energy of AE showed a very similar temporal behavior with electrical resistance variation.…”
Section: Introductionmentioning
confidence: 99%